Influence of growth conditions on glycine reductase of Clostridium sporogenes. - Venugopalan, V (1980)
Cells of Clostridium sporogenes were deficient in glycine reductase activity when grown in a rich medium containing 40 mM each of exogenously added pyruvate and proline or hydroxyproline. These cells lacked the selenoprotein and at least one more protein of the glycine reductase system. Proline or hydroxyproline in the medium also influenced the uptake of glycine by the cells.